Inhibitors and activators for myotoxic phospholipase A2-like toxins from snake venoms – A structural overview - Salvador, Guilherme Henrique Marchi (2024)
Snakebite envenomations result in acute and chronic physical and psychological health effects on their victims, leading to a substantial socio-economic burden in tropical and subtropical countries. Local necrosis is one of the serious effects caused by envenomation, primarily induced by snake venoms from the Viperidae family through the direct action of components collectively denominated as myotoxins, including the phopholipase A2-like (PLA2-like) toxins. Considering the limitations of antivenoms in preventing the rapid development of local tissue damage caused by envenomation, the use of small molecule therapeutics has been suggested as potential first-aid treatments or as adjuvants to antivenom therapy. In this review, we provide an overview of the structural interactions of molecules exhibiting inhibitory activity toward PLA2-like toxins. Additionally, we discuss the implications for the myotoxic mechanism of PLA2-like toxins and the molecules involved in their activation, highlighting key differences between activators and inhibitors. Finally, we integrate all these results to propose a classification of inhibitors into three different classes and five sub-classes. Taking into account the structural and affinity information, we compare the different inhibitors/ligands to gain a deeper understanding of the structural basis for the effective inhibition of PLA2-like toxins. By offering these insights, we aim to contribute to the search for new and efficient inhibitor molecules to complement and improve current therapy by conventional antivenoms.